Impact of downwind sampling location and height on inverse-Gaussian dispersion modeling: A theoretical study - Jones, Heather W; Wang-Li, Lingjuan; Boroujeni, Behdad Yazdani (International Journal of Agricultural and Biological Engineering, 2012)
In the studies of fate and transport of air emissions from animal feeding operations, Gaussian based dispersion models have been commonly used to predict downwind pollutant concentrations through forward modeling approach, or to derive emission rates and emission factors through inverse dispersion modeling approach. In the Gaussian dispersion modeling process, downwind sampling location and sampling height could generate significant impact on accuracy of the model validation, or inverse modeling results based upon field measurements. This study theoretically analyzed the impact of downwind locations and sampling height on Gaussian dispersion modeling. It was discovered that the field sampling needs to be conducted at the locations beyond the plume touching-ground distance, at a downwind distance as short as 5 m for the case scenario with zero rise of emission plume under the atmospheric stability class C, or as long as 297 m for the case scenario with 15 m rise of emission plume under the atmospheric stability class F. In order to measure the PM concentrations of the dispersion plume, the minimum sampling height at the locations within the plume touching-ground distance varied from ground level to as high as almost 14 m, whereas for the locations beyond the plume touching-ground distance, a sampling height of ground level would be acceptable.